Evaluation of Trichoderma inoculants on growth of ginger ( Zingiber Officinable ) Seedlings - Aina Imanina Mokteh @Mohti (2019)
Trichoderma species have long been recognized as agents for the control of plant disease and for their ability to increase plant growth and development. Trichoderma comprises a great number of fungal strains that colonize plants roots as a symbiont
and have properties to stimulate plant growth and development. In this study, an attempt was made to screen Trichoderma inoculants that could act as biofertilizer to improve the growth of ginger seedlings variety Bentong and variety Sarawak.
Trichoderma spp were isolated from forest soil of Mitsubishi-UPMKB Rehabilitated Forest. Trichoderma isolates were identified based on morphological characteristics.
Trichoderma isolates were grown in Potato Dextrose Broth (PDB) and the conidia Suspensionwas used as inoculants. To determine the effect of Trichoderma inoculants towards the growth of ginger seedlings, two Trichoderma inoculants,
(Trichoderma 1 and Trichoderma 2), one fertilizer type (NPK fertilizer), plus a non- amended treatment (negative control) were used. Ginger seedlings treated with
Trichoderma 2 had the greatest height, diameter of seedlings and the number of buds produced of any treatment and were significantly more productive than non-amended seedlings and seedlings fertilized with NPK. The results suggest Trichoderma
biofertilizer could effectively regulated soil chemistry and microbial communities, substantially improves plant growth.
Keywords: biological control; biostimulant; Trichoderma; Ginger (Zingiber officinale)
Projectpaper (B.S.Bi.) - Universiti Putra Malaysia, 2019.
English
Keywords: Plant propagation; Ginger